ANALYSING THE IMPACT OF MODIFIED READING – MIND MAPPING – SHARING (RMS) TECHNIQUE BASED ON TEACHING LEARNING CYCLE (TLC) IN STUDENTS' WRITING DESCRIPTIVE TEXT - Ponda, Sherly; Flora, Flora; Sukirlan, Muhammad (TELL - US JOURNAL, 2025)
This research was initiated to reveal the impact of the modified RMS technique integrated with the TLC, on students’ ability to write descriptive texts. The research aimed to determine whether the modified RMS technique significantly improves students’ descriptive writing achievement. The research design was quantitative by employing  one-group pre-test post-test design. The data were gaied from 32 students using writing tests. Writing performance was evaluated across five aspects: content, organization, vocabulary, grammar, and mechanics. Data were analyzed using paired t-tests. The results demonstrated a statistically significant improvement in students’ writing scores after the treatment (p < 0.001. These finding suggests that the modified RMS technique, when combined with TLC, is effective in enhancing students’ descriptive writing achievement.